Modern sports manager as an object of scientific analysis - Maryna Korolova; Svitlana Stadnyk; Iryna Petrenko; Anastasia Bondar (Kharkiv State Academy of Physical Culture, 2020)
Purpose: to develop a system-structural model of a modern sports manager on the basis of determining the objective and subjective characteristics of his activities. Material and methods: the theoretical analysis and systematization of literary sources on the topic of research made it possible to determine the problematic field of the sports manager's activity in modern conditions. The analysis of documentary materials made it possible to characterize the system of legal regulation of the work of a sports manager, as well as competencies, tasks, functions, and the results of his activities. The application of the method of system analysis made it possible to justify the objective and subjective characteristics of the sports manager. In order to determine the individual and professional qualities of a sports manager, as well as qualities that negatively affect the effectiveness of his professional activity, a survey was conducted among 40 respondents: heads of physical education and sports organizations and among students of the Department of Physical Culture Management of KSAPC. Results: the regulatory component of the training of sports managers is analyzed. A system-structural model has been developed, which consists of a goal and two parts: objective and subjective characteristics of the activities of a modern sports manager. The goals of the activities of the sports manager are determined - to ensure the effective functioning of the sports organization. It is established that the objective characteristics of the activities of a modern sports manager include: competencies, tasks and functions of a sports manager. Subjective characteristics include: professional-role characteristics, professionally important qualities and negative qualities. Conclusions: it turned out that the sports manager is a unique modern profession, which requires continuous improvement, development of practical skills, quick reaction to all changes that take place, increased interest in self-education, and a high level of self-discipline. It is the professionalism, responsibility, initiative and enterprise of managers in any difficult situation that can ensure the physical culture and sports organization success and profit, high efficiency of implemented practical activities.